Pengaruh Keragaman Produk, Persepsi Harga, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen - Yusuf Suhardi; Achmad Syachroni; Agustian Burda; Arya Darmawan (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2020)
The purpose of this study was to determine the effect of product diversity, price perceptions and service quality on consumer purchasing decisions. This research was conducted at the Ardevon Supermarket, Rawamanagun Branch, Jakarta. The research strategy carried out in this study is a casual research strategy. namely research that aims to determine the effect of at least two or more variables and look for cause and effect. The research method used in this research is multiple regression analysis method. The number of samples is 97 people. The sampling method used in this research is purposive sampling. Based on the results of the calculation, the regression obtained a constant of 0.415, b1 0.344, b2 0.243 b3 0.404 in the determinant coefficient (KD) obtained R2 (R Square) of 0.608 or (60.8%). While the remaining 39.2% is influenced by other variables. From the results of the hypothesis test partial t test obtained X1 and Y t count > t table (3.688 > 1.985) then Ho is rejected or Ha is accepted, X2 and Y t arithmetic > t table (3.907> 1.985) then Ho is rejected or Ha is accepted, X3 and Y value t count > t table ( 5.781 > 1.985 ) then Ho is rejected or Ha is accepted with of 5% , in the simultaneous F test between product diversity, price perception and service quality it can be concluded that the F arithmetic value > F table (48.035 > 2 ,70 ) the conclusion is then Ho is rejected or Ha is accepted that, partially and simultaneously there is a positive and significant effect.